Investigation on soil contamination at recently inundated and non-inundated sites - Wölz, Jan; Schulze, Tobias; Lübcke-von Varel, Urte; Fleig, Michael; Reifferscheid, Georg; Brack, Werner; Kühlers, Dirk; Braunbeck, Thomas; Hollert, Henner (Journal of soils and sediments, 2011)
This study was carried out to determine hazards of particle-bound contaminants in rivers to retention areas close to public well fields in the context of flood events. The focus was on the assessment of soil contamination at a planned retention area. Soil core samples were chemically and biologically analyzed. Samples were fractionated to identify and compare contaminant loads and biological effects of soil and flood suspended particulate matter (SPM).
Published online: 13 July 2010
Gesehen am 05.12.2022